Differential Performances in Lesions and Radiotracer of 18F-FDG PET/CT between Multiple Myeloma and Unknown Osteolytic Metastasis - Deng, Chengwen; Han, Dongyan; Zhang, Xiaoying; Lv, Zhongwei; Li, Dan (Current Medical Imaging, 2023)
Purpose: The aim of the study was to investigate the differential performances in lesions and 18F-FDG radiotracer distribution detected by PET/CT between multiple myeloma and unknown osteolytic metastasis. Methods: A retrospective study was performed on 18F-FDG PET/CT imaging of 63 patients with multiple bone destructions without extraosseous primary malignant tumors. By pathological diagnosis, 20 patients were confirmed to have multiple myeloma and 43 patients to have unknown osteolytic metastasis. The whole body was categorized into 8 sites: skull, spine, ribs, pelvis, sternum, clavicle, scapula and limb bone. The length of lesion cross-sections, cortical bone damage, SUVmax and radiotracer distribution were comprehensively compared to differentiate these two diseases. Results: The cross-section lengths and SUVmax of the lesions in 5 sites (e.g., skull, spine, ribs, pelvis, and limb bone) were significantly shorter and lower in the multiple myeloma group than those of the unknown osteolytic metastasis group (P < 0.05). The 18F-FDG was more uniformly distributed in the lesion sites of the skull, spine, ribs, pelvis, scapula, and limb bone in the multiple myeloma group (P < 0.05). In the spine and rib lesion sites, the multiple myeloma group was more likely to show noncortical bone damage than the unknown osteolytic metastasis group (P < 0.05). Conclusion: Differential observations in lesions and 18F-FDG distribution between multiple myeloma and unknown osteolytic metastasis were detected by comprehensively comparing the length of lesion cross-sections, cortical bone damage, SUVmax, and the distribution of radiotracer on18F-FDG PET/CT imaging.
Keywords: cortical bone damage